PEREMPUAN DAN KEMATIAN DALAM SASTRA BANDINGAN: KOLABORASI LAB TEATER CIPUTAT INDONESIA DAN THEATRE COMPANY SHELF JEPANG - Pusposari, Wulan; Anoegrajekti, Novi; Gomo Attas, Sitti (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2023)
The comparative literature used by artists creates a unique experience in supporting the appearance of the works of art they are contemplating. The purpose of writing is to explain the interrelated themes/motifs in the two literary works, namely the short story Rintrik by Danarto and the play Sotoba Komachi by Yukio Mishima and to correlate comparative literary studies in theater collaboration work through testimonies from actors/artists involved in the collaborative program. The research method used is descriptive qualitative by placing the object of research, namely the Indonesian Lab Teater Ciputat group and the Japanese Theater Company shelf which are conducting a performing arts collaboration by crossing two literary works from their respective countries. The results of the study show that the themes/motives of death intertwined in both texts are able to add to the richness of references in the collaborative workspaces of the two groups. The themes or motives of death that are explored in the two literary works through a comparative literary approach convey the intertwining of the two works that were born from different zones/spaces/places. The different perspectives on death from the two main female characters in their respective works will add more image spaces for the two directors in formulating their performances. Comparative literature applied by artist practitioners/practitioners can basically be interpreted as a basis for each individual in responding to knowledge and insight into the field they are involved in to make it wider